Effect of intermittent fasting on circulating inflammatory markers in obesity: A review of human trials - Mulas, Andrea; Cienfuegos, Sofia; Ezpeleta, Mark; Lin, Shuhao; Pavlou, Vasiliki; Varady, Krista A. (Frontiers in Nutrition, 2023)
Obesity is associated with low-grade inflammation. Weight loss, by means of dietary restriction, has been shown to reduce systemic inflammation. Intermittent fasting has recently gained popularity as a weight loss diet, but its effects on inflammatory markers in individuals with obesity have yet to be summarized. Accordingly, this review examined how the two main forms of intermittent fasting, i.e., time restricted eating (TRE) and alternate day fasting (ADF), impact body weight and key circulating inflammatory markers (i.e., C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-alpha), and interleukin-6 (IL-6)), in adults with obesity. Results from this review reveal that TRE with various eating window durations (4–10 h per day) has no effect on circulating levels of CRP, TNF-alpha or IL-6, with 1–5% weight loss. As for ADF, reductions in CRP concentrations were noted when >6% weight loss was achieved. However, ADF had no effect on TNF-alpha or IL-6 concentrations, with this degree of weight loss. Thus, intermittent fasting has little or no effect on key inflammatory markers, but more research is warranted to confirm these preliminary findings.